Article review: Gastroretentive drug delivery system (GRDDS) in captopril - Sutiyah, Siti; Jafar, Garnadi (Science Midwifery, 2025)
Captopril is an antihypertensive drug that belongs to the Angiotensin Converting Enzyme Inhibitor (ACE-Inhibitor) class and is widely applied for first-line therapy. This drug has a pharmacokinetic profile with a short half-life of about 2-3 hours, is easily soluble in water, and is stable under acidic conditions (pH 1.2). However, its stability decreases as the pH increases, making it susceptible to degradation. Absorption of captopril in the stomach does not take place completely due to the low gastro retention time (GTR), causing its bioavailability to be low (around 65%). To increase drug effectiveness, reduce degradation, and improve patient compliance, various drug delivery systems have been developed. One promising approach is the Gastroretentive Drug Delivery System (GRDDS), which is a sustained release drug delivery system deliberately designed to maintain the drug longer in the stomach. This review article aims to examine GRDDS methods that can be applied to captopril, including modification of the matrix and polymer used, in order to obtain a better drug release profile and improve drug characteristics. The literature review was searched using databases namely PubMed, Google Scholar, and Science Direct, with publication year coverage from 2014 to 2024. The keywords used included: “Gastroretentive Drug Delivery System (GRDDS)”.